Safety, Connectivity, and Comfortability as Improvement Indicators of Walkability to the Bus Stops in Penang Island - Sukor, N. S. A.; Fisal, S. F. M. (Engineering, Technology & Applied Science Research, 2020)
This study investigates the determinants of walkability by evaluating assessment indicators by constructing a path model based on on-site data collected in Penang. Based on the path analysis, safety (β2=0.691, t=9.301, p<0.01) and connectivity (β1=0.559, t=8.048, p<0.01) have a positive correlation to walkability. Meanwhile, walkability shows a negative correlation with the number of private vehicles. The findings of this study allow the authorities to focus on enhancing the safety of walking facilities that give access to bus stops which will probably increase the likeliness of using the public bus services. The findings from this study also reveal the underlying factors that can boost the public to adopt walking as an active mode of transport and thus reduce the dependency on private vehicles.